Coleoptera aquáticos associados a troncos submersos em córregos de baixa ordem localizados em diferentes tipos de vegetação do Estado de São Paulo - Valente Neto, Francisco (Universidade Federal de São Carlos, 2011)
Riparian vegetation is source of wood debris in streams so variation in vegetation type promote difference in biomass and richness of these substrates, which affect composition and abundance of insects associated with submerged wood. Aquatic Coleoptera associated with submerged wood debris is pointing out to it importance in the wood breakdown. For evaluated if the vegetation type influences community of aquatic Coleoptera associated with submerged wood debris, we collected submerged wood in eight Atlantic Rainforest streams, eight Cerrado streams and we include two Semideciduous Forest streams. We applied different statistical analysis (redundancy analyses, PERMANOVA and partitioning variation) to test if the taxonomic composition in Cerrado streams was different from Atlantic Rainforest streams and to verify what cause this possible difference, environmental variables, spatial variables or both. We found 1617 organisms distributed in 12 families and 29 genus. We found two boring genus of submerged wood debris for Neotropical region, Lutrochus and Stegoelmis, which play important role to food chain of streams, due to availability of nutrients and microhabitats at wood. The results of taxonomic composition of aquatic Coleoptera associated with submerged wood debris showed differences between Atlantic Rainforest and Cerrado streams, exhibiting that the vegetation type is important factor for the composition of this community. We argued that this is because of differences in composition and structure of vegetation, which cause differences in richness and biomass of submerged wood in streams.
Keywords: Ecologia aquática; Inseto xilófago; Mata ripária; Mata Atlântica; Cerrados; Decomposição de troncos; Insetos minadores; Tipo de vegetação; Boring insects; Riparian vegetation; Vegetation type; Xylophages; Wood breakdown; CIENCIAS BIOLOGICAS::ECOLOGIA